2019
DOI: 10.5664/jcsm.7808
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Intervention Interest Among Individuals With Short Sleep Duration

Abstract: Study Objectives: Over one-third of the United States population sleeps less than the recommended 7 hours a night, which increases risk for chronic diseases. The aim of this study was to evaluate the acceptability of sleep extension interventions and preferences in sleep extension interventions among adults with short sleep duration. Methods: Participants aged 18 to 65 years with self-reported sleep duration ≤ 6.5 hours completed an online survey including reported sleep behaviors, barriers to adequate sleep, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…When wearable devices were self-selectively used, as opposed to randomly assigned, wearable device users had more severe insomnia symptoms at baseline and posttreatment than nonusers 8 . These results dovetail with findings that indicate that sleep-tracking devices are more desirable among individuals with short sleep duration, greater sleep disturbances, and comorbid sleep disorders 78 . Since consumer sleep-tracking devices are advertised as tools to improve sleep, limited data on the efficacy of these programs highlight a potential mismatch between the user’s desire for improved sleep and the device’s ability to improve sleep.…”
Section: Clinical Management Of Insomniasupporting
confidence: 56%
See 1 more Smart Citation
“…When wearable devices were self-selectively used, as opposed to randomly assigned, wearable device users had more severe insomnia symptoms at baseline and posttreatment than nonusers 8 . These results dovetail with findings that indicate that sleep-tracking devices are more desirable among individuals with short sleep duration, greater sleep disturbances, and comorbid sleep disorders 78 . Since consumer sleep-tracking devices are advertised as tools to improve sleep, limited data on the efficacy of these programs highlight a potential mismatch between the user’s desire for improved sleep and the device’s ability to improve sleep.…”
Section: Clinical Management Of Insomniasupporting
confidence: 56%
“…8 These results dovetail with findings that indicate that sleep-tracking devices are more desirable among individuals with short sleep duration, greater sleep disturbances, and comorbid sleep disorders. 78 Since consumer sleep-tracking devices are advertised as tools to improve sleep, limited data on the efficacy of these programs highlight a potential mismatch between the user's desire for improved sleep and the device's ability to improve sleep. Nevertheless, as technology improves and more validation data become available, consumer sleep technologies may play a larger role in clinical settings.…”
Section: Case 9-2mentioning
confidence: 99%
“…The main feature of our intervention is the use of coaching combined with wearable technology to motivate behavior change. In our previous research, the use of consumer sleep technology was rated as highly desirable to individuals with short sleep duration and, in our intervention development, was rated as the most enjoyable aspect of the study [ 42 , 43 ]. The addition of the coach is a critical aspect of this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…"Predictors of intervention interest among individuals with short sleep duration" by Adkins et al moves us in the right direction without being overly ambitious. 2 Adkins evaluated short sleepers for their preferred method of sleep extension. Comparing a digital wrist wearable to telephonic or face-to-face care they found that short sleepers, particularly those self-identified as having a sleep disorder, preferred a wrist wearable.…”
mentioning
confidence: 99%
“…Comparing a digital wrist wearable to telephonic or face-to-face care they found that short sleepers, particularly those self-identified as having a sleep disorder, preferred a wrist wearable. 2 Increased self-monitoring with sleep apps comes with the expectation that clinicians can manage their clinical use. 3,4 Because sleep app users tend to be healthy and have more income, expectations are high.…”
mentioning
confidence: 99%